2006
DOI: 10.1007/s11145-006-9037-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological awareness and learning to read Chinese

Abstract: This study investigated the nature of morphological awareness and its relation to learning to read Chinese characters among 46 Chinese-speaking preschool children. The children took a morphological awareness task, which varied in semantic transparency and morpheme position. Children's vocabulary knowledge and extant character reading ability were measured. Additionally, a character learning task was administered. Results showed that children's performances on morphological awareness were affected by semantic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…This finding is well aligned with the established claim that morphological awareness contributes to school-age students’ performance reading and spelling words or pseudowords (Abu-Rabia et al, 2003; Abu-Rabia, 2007; Saiegh-Haddad, 2013; Taha and Saiegh-Haddad, 2016, 2017). Similar findings have been reported in English (e.g., Deacon and Kirby, 2004; Carlisle and Stone, 2005; Nunes et al, 2006), French (e.g., Casalis and Louis-Alexandre, 2000), Dutch (e.g., Assink et al, 2000), Chinese (e.g., Ku and Anderson, 2003; Chung and Hu, 2007), and Hebrew (Schiff and Lotem, 2011) – to name a few.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is well aligned with the established claim that morphological awareness contributes to school-age students’ performance reading and spelling words or pseudowords (Abu-Rabia et al, 2003; Abu-Rabia, 2007; Saiegh-Haddad, 2013; Taha and Saiegh-Haddad, 2016, 2017). Similar findings have been reported in English (e.g., Deacon and Kirby, 2004; Carlisle and Stone, 2005; Nunes et al, 2006), French (e.g., Casalis and Louis-Alexandre, 2000), Dutch (e.g., Assink et al, 2000), Chinese (e.g., Ku and Anderson, 2003; Chung and Hu, 2007), and Hebrew (Schiff and Lotem, 2011) – to name a few.…”
Section: Discussionsupporting
confidence: 85%
“…Morphological awareness has been found to contribute to school-age students' performance reading and spelling words or pseudowords in English (e.g., Carlisle & Stone, 2005;Deacon & Kirby, 2004;Fowler & Liberman, 1995;Nunes, Bryant, & Bindman, 2006;Singson, Mahoney, & Mann, 2000;Templeton & Scarborough-Franks, 1985;Treiman & Cassar, 1996). Similar findings come from studies in other languages-French (e.g., Casalis & Louis-Alexandre, 2000;Sénéchal, 2000), Dutch (e.g., Assink, Vooijs, & Knuijt, 2000), and Chinese (e.g., Chung & Hu, 2007;Ku & Anderson, 2003)-to name a few.…”
Section: Empirical Support For the Contribution Of Morphological Awarmentioning
confidence: 64%
“…This body of research has convincingly demonstrated that compound awareness is a significant predictor of literacy development among children who are native speakers of Chinese (e.g. Chen, Hao, Geva, Zhu & Shu, 2009; Chung & Hu, 2007; Ku & Anderson, 2003; Li, Anderson, Nagy & Zhang, 2002; McBride‐Chang, Cheung, Chow, Chow & Choi, 2006; McBride‐Chang, Shu, Ng, Meng & Penney, 2007; McBride‐Chang et al, 2008; Shu, McBride‐Chang, Wu & Liu, 2006). Among Chinese–English bilinguals, Wang et al (2009) found that Grade 1 children's English compound awareness explained a small but significant amount of variance (4%) in their Chinese word reading.…”
Section: Within‐language Contribution Of Morphological Awareness To Lmentioning
confidence: 99%
“…Carlo et al, 2004; Chow, McBride‐Chang, Cheung & Chow, 2008; Nunes, Bryant & Olsson, 2003). On the other hand, there is little doubt that vocabulary forms the foundation for developing morphological awareness because knowledge of root words is required to understand and construct compounds (Chung & Hu, 2007; M. Hao, X. Chen, V. Dronjic, H. Shu & R. Anderson, unpublished data; Kuo & Anderson, 2006). In fact, morphological awareness is often considered to represent vocabulary depth (Kieffer & Lesaux, 2008).…”
Section: Within‐language Contribution Of Morphological Awareness To Lmentioning
confidence: 99%